INNOVATIVE PEDAGOGY IN EDUCATION AND CAPACITY BUILDING - P Shirisha; CS Saisudha V (International Journal of Advances in Business and Management Research (IJABMR), 2025)
Capacity building and education are intertwined fields where success in the latter becomes impossible without the former. Capacity building is the process of developing the skills, knowledge, and abilities of the individuals with resource planning to improve their performance and effectiveness. Education is the process of improving critical thinking, awareness, and knowledge enhancement within the conceptual framework of the curriculum. In this digitalisation era, where education is a powerful weapon, its accommodation is fruitless without capacity building. If education is a means of attaining individual empowerment, capacity building is the means of attaining the right knowledge and the right skill set through collaborative networks and training programmes, which act as the foundation to achieve greater heights, matching the dynamics of the society for professional development by meeting the diverse student needs. This paper provides an in-depth analysis of this needful concept through an introduction, a review of literature, the present scenario, the role of various organisations in capacity building in education, an analysis and discussion, and suggestions. It concludes with a future scope that enumerates the possible effects of adopting the mentioned suggestions.